Comparison of intracellular glutathione and related antioxidant enzymes: Impact of two glycosylated whey hydrolysates. (October 2020) - Yu, Haiying; Jing, Yu; Zhang, Xinliu; Qayum, Abdul; Gantumur, Munkh-Amgalan; Bilawal, Akhunzada; Jiang, Zhanmei; Li, Aili
Graphical abstract: Highlights: Glycated hydrolysate A increased more glutathione than glycated hydrolysate B. Glycated hydrolysate A enhanced activities of intracellular antioxidant enzymes. Glycated hydrolysate A reduced cellular lactate dehydrogenase and malondialdehyde. Abstract: The effects of two glycosylated whey hydrolysates (GWH-Gal A and GWH-Gal B) on glutathione (GSH) and related antioxidant enzymes in SGC-7901 cells were evaluated. Two whey glycosylated hydrolysates promoted an increase in reduced glutathione (GSH) in normal SGC-7901 cells. GSH, glutathione peroxidase (GPx), γ-glutamine cysteine synthetaase (γ-GCS), and catalase (CAT) at 1.0 and 2.0 mg/mL in normal SGC-7901 cells were higher in the GWH-Gal A group than in the GWH-Gal B group (P < 0.05). Compared with GWH-Gal B, GWH-Gal A more strongly inhibited decreases in intracellular GSH, GPx, γ-GCS, CAT, and superoxide dismutase (SOD) in H2 O2 -induced SGC-7901 cells. Compared with GWH-Gal B, GWH-Gal A at 1.0 and 2.0 mg/mL effectively inhibited increases in lactate dehydrogenase (LDH) and malondialdehyde (MDA) in H2 O2 -induced SGC-7901 cells (P < 0.05). Therefore, GSH content and related antioxidant enzyme activity levels (GPx, γ-GCS, CAT, SOD) in both normal and H2 O2 -induced SGC-7901 cells were considerably stronger in the GWH-Gal A group than in the GWH-Gal B group.